2021
DOI: 10.3389/fpubh.2021.642630
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Lockdown on Air Quality and Resulting Public Health Benefits in the Mexico City Metropolitan Area

Abstract: Meteorology and long-term trends in air pollutant concentrations may obscure the results from short-term policies implemented to improve air quality. This study presents changes in CO, NO2, O3, SO2, PM10, and PM2.5 based on their anomalies during the COVID-19 partial (Phase 2) and total (Phase 3) lockdowns in Mexico City (MCMA). To minimise the impact of the air pollutant long-term trends, pollutant anomalies were calculated using as baseline truncated Fourier series, fitted with data from 2016 to 2019, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…Within months of the initial outbreak of COVID-19, evidence emerged linking higher ambient levels of fine particulate matter and oxides of nitrogen with increased risk of COVID incidence, severity, and mortality. Within cities, neighborhoods near such sources as roadways and waste facilities-where residents are disproportionately poor and members of minority groups-were at particular risk, helping to explain part of the excess risk of COVID-19 seen in these populations (Ali and Islam 2020;Copat et al 2020;Hendryx and Luo 2020;Hernández-Paniagua et al 2021;Karan et al 2020;Kumari and Toshniwal 2020;Li et al 2020;Liang et al 2020;Naqvi et al 2021;Travaglio et al 2021;Woodby et al 2021;Wu et al 2020;Zhu et al 2020).…”
Section: Air Pollutionmentioning
confidence: 99%
“…Within months of the initial outbreak of COVID-19, evidence emerged linking higher ambient levels of fine particulate matter and oxides of nitrogen with increased risk of COVID incidence, severity, and mortality. Within cities, neighborhoods near such sources as roadways and waste facilities-where residents are disproportionately poor and members of minority groups-were at particular risk, helping to explain part of the excess risk of COVID-19 seen in these populations (Ali and Islam 2020;Copat et al 2020;Hendryx and Luo 2020;Hernández-Paniagua et al 2021;Karan et al 2020;Kumari and Toshniwal 2020;Li et al 2020;Liang et al 2020;Naqvi et al 2021;Travaglio et al 2021;Woodby et al 2021;Wu et al 2020;Zhu et al 2020).…”
Section: Air Pollutionmentioning
confidence: 99%
“…As per the results of the study, it was documented that there was a substantial improvement in air quality during lockdown periods. According to Hernández-Paniagua et al [154], the concentration of NO 2 was reduced by between 10% and 35% in Mexico during lockdown periods. Zalakeviciute et al [155] performed a study in Quito (Ecuador), and the findings of the study show that air quality improved by about 26% to 68%.…”
Section: Impact Of Covid-19 On Air Quality Over South American Countriesmentioning
confidence: 97%
“…Moreover, Sharma et al (2020) [30] and Tobías et al (2020) [31] showed a rise of 17% and 57.7% in O 3 concentrations in India and Barcelona, respectively. Another study aimed at evaluating the Covid-19 lockdown impact on air pollutants levels in the Mexico City Metropolitan Area [32]. This study showed an increase of O 3 concentrations between 16% and 40% at the same sites where NO 2 decreased, and it suggested that in order to reduce the concentrations of O 3, the to be adopted policies should focus on the reduction of the emissions of VOCs from fixed sources.…”
Section: Ozonementioning
confidence: 99%